The Love Poems of May Swenson - Swenson, May (Houghton Mifflin)
May Swenson (1919-1989), escritora norteamericana. Estudió e impartió clases de literatura, fue editora de New Directions Publishers (1959-1966) y presidenta de la Academia de Poetas Americanos (1980-1989). Es autora de los libros de poesía: Another Animal (1954), A Cage of Spines (1958), To Mix with Time (1963), Poems to Solve (1966), Half Sun Half Sleep (1967), Iconographs (1970), More Poems to Solve (1971), The Guess and Spell Coloring Book (1976), New and Selected Things Taking Place (1978), In Other Words (1987), Nature: Poems Old and New (1994), May Out West (1996) y del libro de ensayo: The Contemporary Poet as Artist and Critic (1964).